A Novel Cell-based Luciferase Reporter Platform for the Development and Characterization of T-Cell Redirecting Therapies and Vaccine Development. Issue 3 (20th April 2023) - Grailer, Jamison; Cheng, Zhijie Jey; Hartnett, Jim; Slater, Michael; Fan, Frank; Cong, Mei
Abstract : T-cell immunotherapies are promising strategies to generate T-cell responses towards tumor-derived or pathogen-derived antigens. Adoptive transfer of T cells genetically modified to express antigen receptor transgenes has shown promise for the treatment of cancer. However, the development of T-cell redirecting therapies relies on the use of primary immune cells and is hampered by the lack of easy-to-use model systems and sensitive readouts to facilitate candidate screening and development. Particularly, testing T-cell receptor (TCR)-specific responses in primary T cells and immortalized T cells is confounded by the presence of endogenous TCR expression which results in mixed alpha/beta TCR pairings and compresses assay readouts. Herein, we describe the development of a novel cell-based TCR knockout (TCR-KO) reporter assay platform for the development and characterization of T-cell redirecting therapies. CRISPR/Cas9 was used to knockout the endogenous TCR chains in Jurkat cells stably expressing a human interleukin-2 promoter-driven luciferase reporter gene to measure TCR signaling. Reintroduction of a transgenic TCR into the TCR-KO reporter cells results in robust antigen-specific reporter activation compared with parental reporter cells. The further development of CD4/CD8 double-positive and double-negative versions enabled low-avidity and high-avidity TCR screening with or without major histocompatibility complex bias. Furthermore, stable TCR-expressing reporter cells generated from TCR-KO reporter cells exhibit sufficient sensitivity to probe in vitro T-cell immunogenicity of protein and nucleic acid-based vaccines. Therefore, our data demonstrated that TCR-KO reporter cells can be a useful tool for the discovery, characterization, and deployment of T-cell immunotherapy.